(untitled) (Research, Society and Development, 2021)
The expansion of the use of technology has interfered with different aspects of people’s daily lives, especially teenagers. Even with the benefits of technological advances, the use by people of this age group without adequate and excessive use can generate several risks and relevant changes in mental health. With this in mind, this work sought to identify the impacts of exposure to the internet and social media on the mental health of adolescents. An integrative review was carried out with data collection from Web of Science, Scopus, BVS and Psycnet. Of the total of 245 articles identified, documents were excluded according to the inclusion and exclusion criteria, leaving 40 articles to be allowed. As a result, it was found that technology is essential for the insertion of young people in this world that evolves every day. However, the excessive use of technological resources can affect eating habits, sedentary lifestyle, aggressiveness, substance use or abuse, depression, body image distortions, sleep/wake cycle, hyperactivity, self-mutilation and suicidal ideations. It is unfeasible to think about the new generations disconnected from digital media, for this reason there is a need for a joint action of schools, parents, guardians and the community in general to develop actions that clearly address the risks of the virtual world.